Study of Public Green Open Space in Lima Puluh District, Batu Bara Regency With Remote Sensing Method - Ardi Zikri Muazro; Cut Nuraini; Abdi Sugiarto (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
This research focuses on the Study of Public Green Open Space in Lima Puluh District, Batu Bara Regency with the Remote Sensing Method. This research is included in the type of practical research. Qualitative research method is a research method based on the philosophy of post positivism, used to research on natural object conditions, Data analysis is the process of systematically searching for and compiling data obtained from the results of interviews, field notes, and documentation. Data Reduction Analysis Method, Data Presentation and Drawing Conclusions. The results of the research Green open space are an essential element of a city, in creating city development is required to be environmentally friendly. Environmentally friendly development is mandatory, as a fulfillment of sustainability principles. The natural resources that are owned today must also be felt by future generations. Being in a tropical climate makes Indonesia have abundant natural resources. This is a good thing for the Indonesian state. Many countries are experiencing a natural resource crisis, Indonesia can increase foreign exchange by trading natural resources products to other countries.